Residents' assessment of life in Asilo de Molo. - Cabrias, Ruby Daryl B.
There is an increasing number of elderly living ininstitutions today. This is due to the fact that they are abandoned or don't have a family to take care of them. As such, the researchers are interested to study how the elderly assess their life inside the institution. The primary aim of the study is to know the elderlies' assessment of life in Asilo de Molo. The other objectives of the study are: (1) Describe the organizational structure of Asilo de Molo; (2) Know the profile of the elderly residents in Asilo de Molo; (3) Determine whether elderlies' personal assessment of life in Asilo de Molo varies with the means by which they were admitted in the institution., The study was conducted from August to December 2005 in Asilo de Molo a home for the aged located at Avancena Street City. Data was collected using the survey method. Twenty elderly residents of Asilo de Molo ages 60 years old and over were interviewed using the interview schedule. The respondents are either referred to or personally decided to stay in Asilo de Molo. Key informant interview was also used to gather data. The researchers interviewed the staff to ask about the organizational structure of the institution and the roles and responsibilities of those who compose it, number of elderly residents and their socio-demographic profile and the criteria and process of admission de Asilo de Molo. The organizational structure of Asilo de Molo is composed of the Board of Trustees, the Administrator, the Administrative Council and the five Coordinators namely: the Pastoral Ministry Coordinator, Social Service Coordinator, Residential Care Coordinator, Administrative Service Coordinator and the Marillac Renewal Center Coordinator. The survey reveals that most residents of Asilo de Molo have the age between 60 years old and 85 years old. They are mostly women. Most of them are also single or widowed who have no immediate family member to take care of them. The results also showed that the residents who either personally decide or referred to stay in Asilo de Molo are happy and contented with their life. Even though some referred residents are lonely and want to leave the place, many want to spend the rest of their lives inside the institution. The researchers seek to recommend that more studies about the elderly be done since there are only few researchers pertaining to them. Spending more time with the elderly and interviews with the staffs can lead to better understanding of the study.